Improving Standard of Care Through Introduction of Laparoscopy for the Surgical Management of Gynecological Malignancies. Issue 4 (May 2015) - Bogani, Giorgio; Cromi, Antonella; Serati, Maurizio; Di Naro, Edoardo; Casarin, Jvan; Pinelli, Ciro; Candeloro, Ilario; Sturla, Davide; Ghezzi, Fabio
Abstract : Objective: This study aimed to evaluate the impact on perioperative and medium-term oncologic outcomes of the implementation of laparoscopy into a preexisting oncologic setting. Methods: Data from consecutive 736 patients undergoing surgery for apparent early stage gynecological malignancies (endometrial, cervical, and adnexal cancers) between 2000 and 2011 were reviewed. Complications were graded per the Accordion classification. Survival outcomes within the first 5 years were analyzed using Kaplan-Meier method. Results: Overall, 493 (67%), 162 (22%), and 81 (11%) had surgery for apparent early stage endometrial, cervical, and adnexal cancer. We assisted at an increase of the number of patients undergoing surgery via laparoscopy through the years (from 10% in the years 2000-2003 to 82% in years 2008-2011; P < 0.001 for trend); while the need to perform open surgery decreased dramatically (from 83% to 10%; P < 0.001). Vaginal approach was nearly stable over the years (from 7% to 8%; P = 0.76). A marked reduction in estimated blood loss, length of hospital stay, blood transfusions as well as grade greater than or equal to 3 postoperative complications over the years was observed ( P < 0.001). Surgical radicality assessed lymph nodes count was not influenced by the introduction of laparoscopic approach ( P > 0.05). The introduction of laparoscopy did not adversely affect medium-term (within 5 years) survival outcomes of patients undergoing surgery for apparent early stage cancers of the endometrium, uterine cervix, and adnexa ( P > 0.05 log-rank test). Conclusions: The introduction of laparoscopy into a preexisting oncologic service allows an improvement of standard of care due to a gain in perioperative results, without detriments of medium-term oncologic outcomes.